(untitled) (Journal on studies and research of academic knowledge, 2014)
The scientific culture today is critical to the socio economic and educational development of the countries. In Paraguay it is gradually raising awareness of the scientific and technological culture as a primary tool for communication and practical action that requires citizens to make appropriate decisions in a timely manner. The aim of this paper is to analyze the type of sources of access to information that are viewed by teachers and students of the Teacher Training Institutes of Public Administration in Paraguay (IFDs) to determine the presence of scientific culture and technology in this educational community. This survey was conducted for students and teachers of high schools located in the Eastern and Western Region of the country. It revealed that the study population through television, newspapers and the internet. It is therefore important to strengthen the scientific culture in the IFDs and get teachers and students to incorporate science and related topics for making decisions that affect their daily lives.